EUROPEAN SOCIAL MODEL IN THE 21 CENTURY: REVISITED AND TOWARDS SOCIAL INVESTMENT - Boskovic, Branko (PEOPLE: International Journal of Social Sciences, 2016)
Discussing future of the European Union largely depends on understanding the key principles on which the Union was built. Strong welfare was one among its corner stones and has been ever since. However, numerous crises have affected the way European welfare state is structured and there is a need of modernising it through the European Social Model. It is the model of regulating social policy across the member states, despite the differences among them and it can serve as a good starting point for making sustainable, just and equal union. The new social model needs to be based on the social investment state, as a way of uniting political and economic affairs in order to create competent citizens. On the other hand, the state should be organised in a way to be service oriented with carefully planned ways of investing and spending, so the potential future crises can be overcome with greater ease.